To Comply or Not to Comply: Understanding Developing Country Supply Chain Responses to Russian Sanctions - Haishi Li; Zhi Li; Ziho Park; Yulin Wang; Jing Wu (CESifo GmbH, 2024)
How do firms in neutral developing countries adjust their supply chains in response to geopolitical and economic fragmentation? Do they comply with or circumvent Western sanctions on Russia? Using comprehensive transaction-level bill of lading data from major developing countries, we study these questions in the context of the Russo-Ukrainian War. We find that firms in non-sanctioning countries significantly reduced exports of sanctioned products to Russia (and Belarus) if their headquarters are located in sanctioning countries (i.e., sanctioning MNEs), highlighting MNEs' role in propagating sanctions globally. Domestic firms in developing countries observed a relative increase in such exports, weakening the effect of Western sanctions. Sanctioning MNEs expanded exports of sanctioned products to both sanctioning and Russia-friendly countries, indicating a blend of compliance and non-compliance. Sanctioning MNEs significantly reduced imports from Russia (and Belarus) in financially risky sectors, consistent with the effect of financial sanctions. To strengthen the effectiveness of sanctions, sanctioning countries should use their MNE networks, induce domestic firms in neutral countries to comply, and prevent sanction avoidance of MNEs through indirect exports.
Keywords: F14; F63; O19; 330; global supply chains; geopolitical risk; international conflict